2006
DOI: 10.1037/0021-9010.91.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Becoming team players: Team members' mastery of teamwork knowledge as a predictor of team task proficiency and observed teamwork effectiveness.

Abstract: The authors explored the idea that teams consisting of members who, on average, demonstrate greater mastery of relevant teamwork knowledge will demonstrate greater task proficiency and observed teamwork effectiveness. In particular, the authors posited that team members' mastery of designated teamwork knowledge predicts better team task proficiency and higher observer ratings of effective teamwork, even while controlling for team task proficiency. The authors investigated these hypotheses by developing a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 31 publications
4
56
0
2
Order By: Relevance
“…A team members' knowledge of the concepts of teamwork has been shown to predict better team proficiency. 16 Increased teamwork knowledge, not just clinical knowledge, may therefore improve the management of obstetric emergencies. The wider SaFE study will attempt to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…A team members' knowledge of the concepts of teamwork has been shown to predict better team proficiency. 16 Increased teamwork knowledge, not just clinical knowledge, may therefore improve the management of obstetric emergencies. The wider SaFE study will attempt to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Distributed task knowledge may in turn imply a stronger need for a shared team model such that all members are minded of "who knows what", particularly insofar as divergence in task knowledge may also correspond with less time spent communicating (see for example, Levesque et al, 2001). Indeed, a recent study described by Hirschfeld et al (2006) found that better mastery of "teamwork knowledge" predicted better team task proficiency among US Air Officers in relation to a complex training task and higher observer ratings of effective teamwork after controlling for the former.…”
Section: Proposition 5 Cognitive States -Shared Cognitionmentioning
confidence: 99%
“…Most research has been conducted on two particular aspects of shared knowledge: task (e.g., McItyre & Salas, 1995;Mohrman, 2003) and team knowledge (e.g., Druskat & Pescosolido, 2002;Hirschfeld, Jordon, Field, Giles & Armenakis, 2006;Lankau & Scandura, 2002) with some work looking simultaneously at shared knowledge of both task and team (e.g., Mathieu, et al, 2000;Fleming & Griepentrog, 2003).…”
Section: Proposition 5 Cognitive States -Shared Cognitionmentioning
confidence: 99%
“…As in the VDT approach, high team skill will decrease the probability of an activity to have to be reworked. The level of Teams that have better teamwork skills demonstrate greater teamwork effectiveness (Hirschfeld et al 2006). Teamwork skill will have the same operationalization as functional skill; however it will not affect the task work, but the effectiveness of the coordination mechanisms.…”
Section: Individual Skillsmentioning
confidence: 99%